GREEN, RAPID, SIMPLE, AND AN EFFECTIVE ONE-POT MULTICOMPONENT STRATEGY FOR SYNTHESIS OF NOVEL DIHYDROPYRANO[2,3-C]PYRAZOL-6-AMINES IN AQUEOUS MEDIUM - Azzam, Sadeq Hamood Saleh; Siddekha, Aisha; Pasha, MA (Universal Journal of Pharmaceutical Research, 2020)
Objectives: A series of new dihydropyrano [2,3-c]pyrazol-6-amines in this investigation study, are synthesized by the strategy of one-pot four component reaction in an aqueous medium. Methods: After getting optimum conditions the reaction of different substituted aromatic aldehydes, ethyl acetoacetate, hydrazine hydrate, and phenylacetonitrile catalysed by Sodium hydrogen sulphate NaHSO4 (0.5 m mol) by refluxing in ethanol-water (1:1) (5 ml) and heated at 80 oC. The synthesized molecules product was filtered, washed with water to get nearly pure product in excellent yield. Results: The pure products which were got in a short duration, with excellent yield (80 – 87%). Those new compounds were identified by using spectroscopic techniques FT-IR, 1H-NMR and 13C-NMR. Conclusion: In conclusion, the usefulness of this one-pot multicomponents protocol include easily available starting materials, facile, simple and environment-friendly procedure, and easier separation of products by filtration. Peer Review History: Received 3 February 2020; Revised 9 March; Accepted 27 April; Available online 15 May 2020 Academic Editor: Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com Reviewer(s) detail: Prof Cyprian Ogbonna ONYEJI , Obafemi Awolowo University, Ile-Ife, Nigeria, conyeji@oauife.edu.ng Dr. Md. Shahidul Islam , USTC, Chittagong, Bangladesh, S_i_liton@yahoo.com